Effects of graphene oxide size on curing kinetics of epoxy resin. Issue 47 (1st September 2021) - Chen, Xuebing; Jiang, Weijiao; Hu, Bo; Liang, Zhiming; Zhang, Yue; Kang, Jian; Cao, Ya; Xiang, Ming
Abstract : Effects of graphene oxide (GO) size on the curing kinetics of epoxy resin (EP). Abstract : To study the effects of graphene oxide (GO) size on the curing kinetics of epoxy resin (EP), two kinds of GO were selected and characterized by Fourier transform infrared spectrometry (FT-IR), FT-Raman spectrometry (FTIR-Raman), thermo gravimetric analysis (TGA), dynamic light scattering (DLS), transmission electron microscopy (TEM), X-ray diffractometry (XRD) and X-ray photoelectron spectroscopy (XPS). The results showed that the two kinds of GO had similar chemical structures but different sizes—the average particle size of GO-A was 190.1 nm and that of GO-B was 1510 nm, and GO-A has more oxidizing groups on its surface. The two kinds of GO were separately added to EP, and the curing kinetics of GO/EP composites and neat EP were investigated through differential scanning calorimetry (DSC). It can be seen that the addition of GO promoted the curing process of the EP system, and GO-A had a more significant catalytic effect. Furthermore, the curing activation energy ( E a ) was calculated by Kissinger model, and the change of E a in the whole curing reaction process was studied by Ozawa method to further understand the curing mechanism. It showed that the apparent E a of EP system increases with the increase of the conversion rate, and E a of EP-A is obviously lower in the early curing stage. However, as the curing reaction proceeds, E a of EP-B is a little lower than that of EP-A in the later curing stage. But EP-A has the lowest E a combined with the whole process from Kissinger method. To sum up, it can be concluded that the curing process of EP can be promoted by adding GO and the smaller size (190.1 nm) of GO had a greater effect and lower E a than the GO with particle size of 1510 nm. And the related mechanisms were discussed and analyzed.